Impacts of Aerobic Capacity, Liver Function, and Metabolism on Brain Health. (20th December 2022) - Lysaker, Colton R; Troutwine, Benjamin R; Strope, Taylor A.; Franczak, Edziu M; Allen, Julie A; Chauhan, Munish; Harris, Janna L; Thyfault, John P; Wilkins, Heather M
Abstract: Background: Aerobic capacity (VO2 max) strongly influences biological functions including both liver and brain function. Low aerobic capacity has far reaching impacts with both increased risk of non‐alcoholic fatty liver disease (NAFLD) and Alzheimer's disease (AD). Previous work has shown that poor liver function was associated with decreased cognitive function and increased risk of AD. In addition, diet and lipid metabolism play a critical role in brain health, however, the full relationship between these factors and AD risk needs to be elucidated. Method: We assessed brain mitochondrial function and AD pathology in rats selectively bred for aerobic capacity (low‐capacity runners or high capacity runners, bred over 43 generations). Mitochondrial function was assessed using Seahorse XF technology and spectrophotometric Vmax assays. Phosphorylated tau and Aβ levels were analyzed using western blotting and ELISAs. We assessed outcomes at 12, 18, 24, and 28 months. A separate cohort of rats were fed a low‐fat diet (LFD), high fat diet (HFD), or high fat diet with bile acid sequestrant (HFD+BA) and followed from age 6 to 12 months. Barnes and Y‐maze were performed to measure cognitive outcomes. MRI/MRS was completed to measure hippocampal volume and neurochemical profiles. Result: Mitochondrial function parameters were different between groups and with different diets in both brain and liver. Overall LCR animals had reduced brain mitochondrial function and reduced resilience with long term HFD. LCR rats had increased phosphorylated tau levels. Female rats with a low intrinsic aerobic capacity (LCR) have significantly higher levels of Aβ42 when compared to rats with a high intrinsic aerobic capacity (HCR). LCR rats performed worse on the Y‐maze beginning at 10 months of age irrespective of diet. Conclusion: Aerobic capacity and diet affect brain health during aging. Liver function appears to play a large role in brain health outcomes. We continue to analyze MRI/MRS and cognitive data in correlation with liver function.